Comparison of extrusion processes in sheet-bulk metal forming for production of filigree functional elements. (August 2019) - Pilz, F.; Merklein, M.
Abstract: Increasing demands on forming processes with regard to the functional integration of components and lightweight construction pose a challenge to conventional processes. The application of bulk forming operations on sheet metal semi-finished products, also called sheet-bulk metal forming (SBMF), is a suitable approach to meet these challenges. Insufficient die filling and high tool loads are limiting factors in SBMF processes. In order to overcome these limitations in the future, it is necessary to provide appropriate measures. The basis for this is a comprehensive understanding of the manufacturing process for lock and gear toothing by extrusion on sheet metal. This paper identifies requirements for extrusion processes and establishes two corresponding processes. In addition to carrying out experimental investigations, numerical models are developed and validated with the aid of forming tests. In combination with experimental analysis, the simulation models are then used to investigate similarities and differences between both processes. During the processing of the steel 1.0338 (DC04), the investigations showcase a process class specific material flow, demanding tool loads and challenges in the production of filigree functional elements.